Photon Counting (IntechOpen, 2023)
Photon counting is a unified name for the techniques using single-photon detection for accumulative measurements of the light flux, normally occurring under extremely low-light conditions. Nowadays, this approach can be applied to the wide variety of the radiation wavelengths, starting from X-ray and deep ultraviolet transitions and ending with far-infrared part of the spectrum. As a special tribute to the photon counting, the studies of cosmic microwave background radiation in astronomy, the experiments with muon detection, and the large-scale fundamental experiments on the nature of matter should be noted. The book provides readers with an overview on the fundamentals and state-of-the-art applications of photon counting technique in the applied science and everyday life.